Instilling a Spirit of Global Diversity Through Picture Story Books Based on the Ngelawang Barong Tradition - Sari, Dewa Ayu Gita Noviana; Wiarta, I Wayan (Jurnal Pendidikan Multikultural Indonesia, 2024)
The decline in tolerance and difficulty in accepting cultures outside one's own are problems that must be addressed immediately. Apart from that, the results of observations show that there are no supporting books that specifically discuss character values with the dimension of global diversity. This research aims to describe the design, analyze the feasibility and effectiveness of picture story book media based on the Ngelawang barong tradition. This development research uses the ADDIE model. Data collection methods use questionnaires and non-test methods in the form of assessment rubrics. The subjects of this research were 25 students. The data analysis techniques used are quantitative descriptive techniques and inferential statistics. The percentage results obtained were 80% from design experts, 96% from material content experts, 97% from instructional design and learning media experts, 96.3% from individual tests, and 96.4% from small group tests. The results of the effectiveness test using the dependent t-test technique obtained a tcount result of 24.149, while ttable was 1.71. This shows that the tcount is greater than the ttable, so H0 is rejected and H1 is accepted. So it can be concluded that the use of picture story book media based on the Ngelawang barong tradition can increase student enthusiasm and increase the character value of global diversity dimensions so that the learning process can run more optimally.